2014
DOI: 10.1007/s11605-014-2543-z
|View full text |Cite
|
Sign up to set email alerts
|

Adenomas of the Ampulla of Vater: A comparison of Outcomes of Operative and Endoscopic Resections

Abstract: There is no significant difference between endoscopic and local operative resections of benign adenomas of ampulla of Vater; recurrences are more common when two or more endoscopic resections are required for complete tumor removal. Appropriate adenomas for endoscopic resection included tumors <3.6 cm that do not extend far enough intraductally (on EUS) to preclude an endoscopic snare ampullectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 22 publications
1
33
0
7
Order By: Relevance
“…Endoscopy was associated with shorter intervention (51 vs. 191 min, p < 0.001) and decreased blood loss (0 vs.100 mL, p < 0.001). Overall, surgical patients experienced more postoperative complications Comparative studies on these less invasive alternatives reported that EA was associated with lower morbidity compared to SA (7,12). The comparison with previous studies is somehow awkward since they did not focus on postoperative complications, but rather reported overall morbidity without using a validated grading system (7,12).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Endoscopy was associated with shorter intervention (51 vs. 191 min, p < 0.001) and decreased blood loss (0 vs.100 mL, p < 0.001). Overall, surgical patients experienced more postoperative complications Comparative studies on these less invasive alternatives reported that EA was associated with lower morbidity compared to SA (7,12). The comparison with previous studies is somehow awkward since they did not focus on postoperative complications, but rather reported overall morbidity without using a validated grading system (7,12).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, surgical patients experienced more postoperative complications Comparative studies on these less invasive alternatives reported that EA was associated with lower morbidity compared to SA (7,12). The comparison with previous studies is somehow awkward since they did not focus on postoperative complications, but rather reported overall morbidity without using a validated grading system (7,12). Notwithstanding, a landmark study by Ceppa et al showed an overall morbidity of 18% for EA compared to 42% for patients undergoing surgery (p = 0.006) (7); these findings are indeed consistent with the present results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations